Virtual Subinternships in the COVID Era: Lessons Learned from Three Institutional Experiences. Issue 3 (24th March 2023) - Reghunathan, Meera; Dekker, Paige K.; Belza, Caitlyn C.; Kim, Kevin G.; Phillips, Brett T.; Fan, Kenneth L.; Brown, David A.; Gosman, Amanda A.; Lance, Samuel H.
Abstract : After the cessation of all in-person visiting rotations during the coronavirus 2019 pandemic, many programs developed virtual rotations as an alternative for the recruitment and education of prospective applicants. In this study, we developed a consortium of three institutions each with a unique virtual subinternship and prospectively surveyed participating students in order to reflect and improve upon future rotations. All students participating in virtual subinternships at three institutions were administered the same pre subinternship and post subinternship electronic surveys. Subinternship curricula were developed independently at each respective institution. Fifty-two students completed both surveys, for an overall response rate of 77.6%. Students' primary objectives were to evaluate their fit with the program (94.2%), interact with residents (94.2%), gain faculty mentorship (88.5%), and improve didactic knowledge (82.7%). Postrotation surveys revealed that over 73% of students reported having met all of these objectives over the course of the rotation. On average, students ranked programs 5% higher overall after the rotation ( P = 0.024). Postrotation results showed that the majority (71.2%) of students perceived the virtual subinternship as slightly less valuable than in-person subinternships but that all students would participate in a virtual subinternship again. Student objectives can be successfully met using the virtual format for subinternships. The virtual format is also effective in enhancing the overall perception of a program and its residents. Although students still prefer in-person subinternships, our results suggest that virtual rotations are more accessible and very capable of meeting student goals.